Long‐ and short‐term outcomes in renal allografts with deceased donors: A large recipient and donor genome‐wide association study. Issue 6 (1st February 2018) - Hernandez‐Fuentes, Maria P.; Franklin, Christopher; Rebollo‐Mesa, Irene; Mollon, Jennifer; Delaney, Florence; Perucha, Esperanza; Stapleton, Caragh; Borrows, Richard; Byrne, Catherine; Cavalleri, Gianpiero; Clarke, Brendan; Clatworthy, Menna; et al.
Abstract : Improvements in immunosuppression have modified short‐term survival of deceased‐donor allografts, but not their rate of long‐term failure. Mismatches between donor and recipient HLA play an important role in the acute and chronic allogeneic immune response against the graft. Perfect matching at clinically relevant HLA loci does not obviate the need for immunosuppression, suggesting that additional genetic variation plays a critical role in both short‐ and long‐term graft outcomes. By combining patient data and samples from supranational cohorts across the United Kingdom and European Union, we performed the first large‐scale genome‐wide association study analyzing both donor and recipient DNA in 2094 complete renal transplant‐pairs with replication in 5866 complete pairs. We studied deceased‐donor grafts allocated on the basis of preferential HLA matching, which provided some control for HLA genetic effects. No strong donor or recipient genetic effects contributing to long‐ or short‐term allograft survival were found outside the HLA region. We discuss the implications for future research and clinical application. Abstract : The largest multicenter genome‐wide association study to date on short‐ and long‐term renal transplantation outcomes finds no loci outside the HLA region, highlighting challenges in phenotypic heterogeneity and sample size while also providing a reference dataset for future meta‐analyses.